Project HOPE: American nurses in Brazil (1973) - Laís de Miranda Crispim Costa; Tânia Cristina Franco Santos; Luiz Otávio Ferreira; Antônio José de Almeida Filho; Regina Maria dos Santos; Elaine Lázaro Alcántara
ABSTRACT Objective: to describe the reality of nurses of Project HOPE and discuss the repercussion of their performance in relation to the reconfiguration of nursing in Alagoas State. Method: social-historical study, whose primary sources were documents filed in the Laboratory of Documentation and Research in History of Nursing, granted by this project; oral testimonies resulting from the transcription of interviews of US nurses and the VeNeta Masson's'logbook, coordinator nurse of the ship. The discussion of the data was based on Pierre Bourdieu's theory. The project was submitted to the Ethics Committee and approved by it. Results: The actions of the American nurses exposed the shortage of this type of professional in the area, as well as the precarious health conditions in the region. Conclusion: the symbolic capital of these nurses has contributed to the reconfiguration of the nursing field in Alagoas State.